O etiki in spolnosti v mladinskih delih Dese Muck - Švajncer, Marija (Otrok in knjiga, 2010)
The article deals with the explicit and implicit treatment of ethics and sexuality in the juvenile works of the Slovene writer Desa Muck. Ethics is an important dimension and immanent topic of the writer's creative opus. The ethic message of her literature is a direct and also indirect means of educating teenage readers. Educating and exerting well-intentioned influence upon young persons does not in any way curtail the artistic value of the author's writing, characterized by humour, vivid imagination, witty choice and delineation of literary figures, as well as humane and moral engagement. Regarding the style and expression, the author is innovative and free in applying several levels of the contemporary Slovene language. Theoretically her writing is based on the realistic understanding of the philosopher Igor Primorac; for him sexuality is just an extension and one of the components of ethic attitude, for the writer just a part of human relations.
Keywords: juvenile literature; Muck, Desa, 1955-; mladinska književnost; etics; young adult literature; sexuality; literarne študije; etika; ethics; sexual intercourse; spolnost